Convert the equation from vertex form to standard form y=−4(x+5)2−3 .(1 point)

Responses

y=16x2+160x+397
y equals 16 x squared plus 160 x plus 397

y=−4x2−40x−103
y equals negative 4 x squared minus 40 x minus 103

y=16x2+160x+412
y equals 16 x squared plus 160 x plus 412

y=−4x2−25x−3

1 answer

To convert the equation from vertex form \( y = -4(x + 5)^2 - 3 \) to standard form, we can start by expanding the vertex form:

  1. Expand \( (x + 5)^2 \): \[ (x + 5)^2 = x^2 + 10x + 25 \]

  2. Substitute this back into the equation: \[ y = -4(x^2 + 10x + 25) - 3 \]

  3. Distribute the \(-4\): \[ y = -4x^2 - 40x - 100 - 3 \]

  4. Combine the constants: \[ y = -4x^2 - 40x - 103 \]

Thus, the standard form of the equation is: \[ \boxed{y = -4x^2 - 40x - 103} \]

So, the correct response is: y=−4x²−40x−103.

Similar Questions
  1. QuestionConvert the equation from vertex form to standard form y=−4(x+5)2−3 .(1 point) Responses y=−4x2−25x−3 y equals
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions